Contextual Learning Model In Improving The Character Of Students In Islamic Religious Education Subjects At SMP Muhammadiyah 7 Colomadu - Muslimah, Mutiah; Inayati, Nurul Latifatul (LPPI, 2023)
This research is motivated by a common learning phenomenon in Indonesia, teachers still use conventional learning models, one solution to solve these problems is how teachers apply learning models to Islamic religious education subjects, including contextual learning models or Contextual Teaching and Learning (CTL).The objectives of this study are: 1) Describe the application of contextual learning models to Islamic religious education teachers in improving the character of SMP Muhammadiyah 7 Colomadu , 2) Identify obstacles to the application of contextual learning models of Islamic religious education teachers in improving the character of SMP Muhammadiyah 7 Colomadu. This research is a qualitative research that uses a phenomenological approach. Regarding the location of the study, namely SMP Muhammadiyah 7 Colomadu, informants who were used as sources were school principals, PAI subject teachers and students. Data collection techniques in the field use observation, interviews and documentation. The results of the study explained that First, the implementation of the contextual learning model in Islamic religious education subjects had a positive impact and greatly improved the character of students of SMP Muhammadiyah 7 Colomadu. Second, the obstacles to the implementation of this contextual learning model are students who do not pay attention to the teacher and some sleep during learning, from these obstacles PAI teachers have their own efforts to solve the character of students, one of which is habituation and sensitivity to the surrounding environment. The implications of this research are the importance of improving the character of students in learning, especially learning Islamic religious education through contextual learning models.